HUBUNGAN INTENSITAS PENGGUNAAN GADGET DENGAN PERILAKU TEMPER TANTRUM PADA ANAK USIA 3-5 TAHUN DI ERA PANDEMI COVID-19 - Khatia Azzahra (2023)
During the Covid-19 pandemic, all Indonesian people were required to carry out all activities from home so there was an increase in the intensity of using gadgets, including in children. The use of gadgets with high intensity can have a negative impact on the index of early childhood development, one of which is the social-emotional dimension. One of the problems in the emotional dimension that often occurs in early childhood is temper tantrums. This study aims to determine the relationship between the intensity of using gadgets and the behavior of temper tantrums in children aged 3-5 years during the Covid-19 pandemic. This research is a cross-sectional study. Data collection was carried out using simple random sampling technique with a total sample of 62 respondents with a research instrument using a questionnaire. Data were analyzed based on the characteristics of the respondents, univariate analysis, and bivariate analysis using the ChiSquare test obtained p-value = 0.0039. It can be concluded that there is a relationship between the intensity of using gadgets and the behavior of temper tantrums in children aged 3-5 years during the Covid-19 pandemic.